The intervention of the emergency psychologist: the SIPEM SoS Emilia Romagna during the first lockdown from COVID-19: A retrospective study. - Cervellione, Brenda; Rossi, Sandra; Carbone, Roberta; Ferracane, Giuseppina; Lombardo, Ester M.C.; Pedrelli, Enrica; Sozzi, Anna; Artioli, Giovanna; Sarli, Leopoldo; Iacolino, Calogero (Acta Biomedica Atenei Parmensis, 2021)
Background and purpose of this work: WHO 11 March 2020 declares that Sars-Cov-2 infection is not only a health emergency but must be considered a pandemic. Covid-19 required the urgency of a new psychological intervention model to better address the crisis and ensure a direct support response to the people involved in the pandemic. The present study aimed to detect the symptoms and reactions of the population with respect to the event. The survey was carried out by describing the clinical symptoms that emerged from the triage card used by SIPEM SoS Emilia Romagna (Italy), connoting the criteria of emergency psychology. Methods: A retrospective quantitative study was conducted on 288 psychological triage cards. Results: only 11% of users who ask for support say they are positive while 85% report not having contracted the virus. Of the total, 40.9% call for psychological support in the management of anxiety symptoms, a need also reported by 55% of the subsample who declared previous psychological problems. In reaction to the pandemic event, 51.1% of the total refers to coping resources and availability for help. Discussions: the need for support of the population to manage symptoms highlights the need for early interventions, also to facilitate that slice of the population that does not have effective individual coping strategies and resources available to help. Conclusions: it can be deduced that interventions during these types of emergencies must be timely and aimed not only at those affected but also at the general population.